The Impact of Quizizz-Based Learning on Students’ Creativity and Learning Outcomes in Islamic Cultural History - Royyanatul Mahbubah; Rofiatul Hosna; Asriana Kibtiyah (Journal of Contemporary Islamic Education, 2026)
The development of digital technology has encouraged the use of digital learning platforms to support the learning process in schools. One of the digital learning platforms that is widely used is Quizizz, which offers interactive and technology-based learning. This study aims to analyze the effect of using a Quizizz-based digital learning platform on students’ creativity and learning outcomes. This study uses a quantitative approach with a Quasi-Experimental Design employing a Pretest–Posttest Control Group Design. Research data were obtained through questionnaires to measure learning creativity and tests to measure students’ learning outcomes. The collected data were then analyzed using Simple Linear Regression, Difference Test (Paired Sample T-Test), and Multivariate Analysis of Variance (MANOVA). The results of the study show that the use of Quizizz in the learning process has a significant effect on students’ creativity and learning outcomes. This is evidenced by the significance value of the simple linear regression test of 0.005 < 0.05, the Paired Sample T-Test of 0.000 < 0.05, and the MANOVA test of 0.000 < 0.05. Therefore, the use of Quizizz can be an effective alternative digital learning medium for improving students’ creativity and learning outcomes.